The Impact of IT Integration in Human Resource Management on Employee Productivity: A Study of Afghanistan's NGOs (Salam International Academic Journal, 2024)
This research investigates the role of Information Technology (IT) in enhancing Employee Productivity within Afghanistan's non-governmental organizations (NGOs), focusing on IT-driven HR practices, IT knowledge, IT innovation, and IT infrastructure. Using a quantitative survey research design, data were collected from HR and IT professionals in the telecom, banking, and university sectors in Afghanistan, with 206 valid responses obtained. The findings reveal a strong and positive association between IT-driven HR practices and Employee Productivity, confirming their critical role in streamlining HRM processes. IT knowledge also demonstrated a significant positive effect, emphasizing the importance of employee IT competencies in achieving productivity gains. In contrast, IT innovation and IT infrastructure had limited and statistically non-significant effects, suggesting that their influence on productivity may be indirect or context-dependent. This research highlights the importance of implementing IT-driven HR systems and enhancing IT-related knowledge to improve organizational outcomes. NGOs in Afghanistan should prioritize investments in IT-based HR practices and employee IT training to optimize productivity. Further research is recommended to discover the underlying mechanisms through which IT innovation and infrastructure may influence productivity and to investigate additional contextual factors within Afghanistan’s unique organizational landscape.
Keywords: Information Technology; Employee Productivity; IT-driven HR practices; IT knowledge; Non-governmental Organizations; IT innovation; IT infrastructure; HR professionals; Afghanistan; IT-based HR systems